A content analysis of Singapore public libraries’ Facebook posts - Lim, Benita Suet Ting (2018)
The burgeoning global popularity of social media is evident in several fields and communities, including the libraries and librarians. In the local context, digital traces of the Public Libraries Singapore (PLS), which is a network of 26 public library branches, can be found on three social media platforms. As of August 2018, the PLS Facebook page boasts the largest social media following in comparison to its Twitter and Instagram accounts.